Early total reconstruction for a Gustilo type IIIB open forearm fracture associated with avulsion injury of multiple extensor tendons: A case report - Shuya Nohmi; Masahiro Suzuki; Yukiko Sakamoto; Ryo Nakano; Hikaru Kamada (Trauma Case Reports)
Gustilo type IIIB open forearm fractures associated with avulsion injuries of multiple extensor tendons are difficult to reconstruct. Not only are bones, nerves, blood vessels, and soft tissues injured, but also tendons directly related to hand function.A 74-year-old man sustained an injury to his dominant right hand after being hit by a heavy pulley. The patient was diagnosed with a Gustilo type IIIB open forearm fracture, and multiple extensor tendons were avulsed from the musculotendinous junction. On the day of injury, the radius was fixed using a volar locking plate, and the ulnar head was fixed to the radius. On the fourth day, the avulsed extensor tendons were reconstructed using tendon transfer, and the exposed tendons and soft tissue defects were covered using a free anterolateral thigh flap on the seventh day. Three years after the injury, the patient had no difficulty in performing activities of daily living.Single-stage reconstruction allows for early rehabilitation. We believe that the more complex and severe the injury is, the more we should aim to repair the injured tissue as early as possible, that is, early total reconstruction.